Silver Nanoparticles Decorated in In Situ Reduced Graphene Oxide Nanohybrids Improved Properties in Poly(vinylidene fluoride)/Poly(methyl methacrylate) Blends - Afifeh Khorramshokouh; Hesam Ramezani; Mehdi Sahami; Mehdi Sharif; Behzad Vaferi (International Journal of Polymer Science)
In this paper, reduced graphene oxide decorated with silver nanoparticle (rGO-Ag) nanohybrids were prepared using an environmentally friendly approach and incorporated as reinforcement in poly(vinylidene fluoride)-poly(methyl methacrylate) blends via a melt mixing process. The microstructure of rGO-Ag nanohybrids and its effect on the microstructure, mechanical, thermal, and electrical properties of the PVDF/PMM/rGO-Ag was studied using Fourier transform infrared (FTIR), Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), tensile, thermogravimetric analysis (TGA), and impedance spectroscopy methods. FTIR and TEM analysis confirmed that rGO-Ag successfully synthesized and Ag nanoparticles are located on the rGO surface. The tensile analysis demonstrated that incorporating 1 wt.% of rGO-Ag in PVDF/PMMA blend increases Young’s modulus and strength of nanocomposite up to 31% and 35%, respectively. The Halpin-Tsai model was also used for PVDF/PMMA/rGO-Ag nanocomposites, and the results confirmed that this model works well to predict the tensile modulus. Impedance spectroscopy analysis showed that the presence of rGO-Ag nanohybrids in PVDF/PMMA blend effectively enhanced the conductivity of PVDF/PMMA blend. TGA results demonstrated that the presence of rGO-Ag nanohybrids enhanced the thermal stability of nanocomposites and increased the degradation temperature of PVDF/PMMA/rGO-Ag nanocomposites in the range of 20°C compared to PVDF/PMMA blend.